A simple, light clip‐cage for experiments with aphids. (11th January 2018) - Haas, Jucelaine; Lozano, Everton R.; Poppy, Guy M.
Abstract: Clip‐cages are a useful experimental tool for confining small insects to leaves when aiming to study their behaviour and/or other biological parameters. Nonetheless, clip‐cages are usually heavy and may damage the leaves, which renders them less useful for numerous research studies. We propose a very simple clip‐cage, which is cheap, extremely light, and easy to make and handle, and which has less of the negative, damaging nature of traditional clip‐cages. Each clip‐cage was prepared using two discs of foam‐floating tubes: one for support and one for confining the insects. On the upper surface of the latter, a rectangle of microperforated plastic flower sleeve (8 cm 2 ) was glued using a nontoxic glue stick. To bind the two parts to the leaf, four staples (23/13) were used. We tested the clip‐cages by confining Myzus persicae to Brassica oleracea and Brassica rapa leaves and then compared the results obtained with those acquired using classic clip‐cages. Each foam clip‐cage was assembled in less than 2 min. Our experiments confirmed the M. persicae escape rate of 6%, which compared favourably with the escape rate of 40% for the classic clip‐cage. Furthermore, the clip‐cages did not interfere with the growth rate of the aphids. The foam clip‐cages are up to 200% cheaper than the classic clip‐cages. They are light, durable, easily put together and transported, and have the potential to be easily used in field experiments.